Implementation of Solution-Focused Brief Counseling (SFBC)-Based Counseling Services in Addressing Learning Anxiety Among SMK Students - Elik Kurnia; Tety Kumalasari; zaitun; Encik Abdulhajar; Dody Irawan (Program Studi Bimbingan dan Konseling Universitas PGRI Semarang, 2026)
Learning anxiety is a common psychological issue among vocational high school students that affects concentration, self-confidence, and academic performance. This study aims to describe the implementation of Solution-Focused Brief Counseling (SFBC) in addressing students’ learning anxiety in a vocational high school setting. A qualitative research approach was employed using in-depth interviews, observations, and documentation involving students experiencing learning anxiety and school counselors. The results indicate that SFBC enables students to recognize their personal strengths, set achievable learning goals, and develop practical solutions to overcome learning difficulties. Following the counseling sessions, students demonstrated reduced learning anxiety, increased self-confidence, and more positive learning behaviors. These findings suggest that SFBC is an effective and applicable counseling approach for managing learning anxiety and supporting students’ academic and emotional development in vocational schools.